Pendampingan Perancangan Rencana Pembelajaran Inovatif: Strategi Transformasional Menuju Pendidikan Berkualitas - Umamah, Zainatul; Anifah, Siti (Humanist Journal, 2024)
Quality education requires innovative and adaptive learning planning according to current developments. This article discusses strategic steps that can be taken to create motivating and relevant learning experiences. Progressive education requires an innovative approach in designing learning plans. This article outlines a series of strategic steps that can be taken to create a dynamic learning experience that is in line with current needs. By exploring the concept of in-depth understanding of student needs, readers are invited to understand the importance of differentiation as the main basis. Collaborative and team learning is the focus of the next section, providing concrete examples of the implementation of teamwork in the learning process. Evaluation of innovation and continuous adjustment concludes, emphasizing the importance of continuous reflection in improving the effectiveness and relevance of learning plans. This article uses a literature review research method, namely a literature study by taking sources from scientific journals. The aim of this article is to provide inspiration and practical guidance to readers to develop learning plans that are not only innovative but also relevant and responsive to changes in the world of education.